THE EFFECTS OF GROUP WORK WITH CREATIVE WRITING TECHNIQUE ON STUDENTS’ NARRATIVE WRITING AT DAYANU IKHSANUDDIN UNIVERSITY BAUBAU - Ary Irjayanti Herman (English Education Department, 2019)
The aims of this research were to find out whether the use of Group Work with Creative Writing Technique improves the students’ writing skills and interest of students’. Quasi-experimental design was applied in this research. The experiment of this research was third semester students of English Educational Study Program of Dayanu Ikhsanuddin Baubau, in 2014/2015 academic years. The sample of the research was 80 students which consist of two classes; in experimental 40 students and control class 40 students. There were two instruments in getting the data on this research : the test on narrative writing as well as questionaires to get the interest. The researcher used descriptive and inferential for test data analysis. Meanwhile , likert cale for interest. The findings were: (1) the application of Group Work with Creative Writing technique got the students’ writing performance improved, (2) the application of Group Work with Creative Writing technique is interesting to the students on writing class. On the other hand, the application of Group Work with Creative Writing technique improved the students’ writing performance on content, organization, vocabulary, language use and mechanics and they got very high interest on the application of Group Work with Creative Writing technique in teaching writing.